DENTAL IMPLANTS AS THE MOST APPROPRIATE METHOD OF ANCHORING FIXED PROSTHESES (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Dental implants are currently the most appropriate solution to tooth loss. This article discusses the positive aspects of using dental implants to improve the quality of life of patients in the treatment of partial and complete tooth loss. The advantages, disadvantages and complications of different treatment methods are also shown. The main factors directly affecting the restoration of tooth structure are emphasized. The prosthetic and surgical phases of treatment are defined, as well as the optimal choice of materials, techniques and conditions for dental implantation. The importance of each method and the involvement of each stage in the patient's dental treatment is shown. Based on the material presented, implant-supported removable dentures are the only method that is highly effective and, in some cases, produces good results.